The implementation of novel collaborative structures for the identification and resolution of barriers to pluripotent stem cell translation. - Brindley, D; French, A; Suh, J; Roberts, M; Davies, B; Pinedo-Villanueva, R; Wartolowska, K; Rooke, K; Kramm, A; Judge, A; Morrey, M; Chandra, A; et al. (2013)
Increased global connectivity has catalyzed technological development in almost all industries, in part through the facilitation of novel collaborative structures. Notably, open innovation and crowd-sourcing-of expertise and/or funding-has tremendous potential to increase the efficiency with which biomedical ecosystems interact to deliver safe, efficacious and affordable therapies to patients. Consequently, such practices offer tremendous potential in advancing development of cellular therapies. In this vein, the CASMI Translational Stem Cell Consortium (CTSCC) was formed to unite global thought-leaders, producing academically rigorous and commercially practicable solutions to a range of challenges in pluripotent stem cell translation. Critically, the CTSCC research agenda is defined through continuous consultation with its international funding and research partners. Herein, initial findings for all research focus areas are presented to inform global product development strategies, and to stimulate continued industry interaction around biomanufacturing, strategic partnerships, standards, regulation and intellectual property and clinical adoption.